Islamic with Turkish Connections: Atiya’s and Zeyneb’s Counter-narratives to the West - Hasan, Md. Mahmudul (Taylor & Francis Group, 2021)
South Asian Atiya Fyzee and her Turkish contemporary Zeyneb Hanoum were epistolary travel writers. Despite their variant geographical identities, both had Turkish connections and share similarities in their work. Both made trips to Europe in the early twentieth century when international travel was not as common as it is today. The preferred mode of long-distance travel then was by sea, as the faster means of air transportation began to be widely used on a commercial basis only in the 1950s and 1960s. The travel accounts of these two writers demonstrate striking commonalities, especially with regard to Islamic devotional expressions and counter-narratives to the West. While Atiya in her writing responded to negative portrayals of Indians in colonial discourse, Zeyneb wrote back to the dominant Western representation of Turkish women as homogenously passive, hidden and silenced in the harem. Given these different backgrounds and positionalities, their counter-narratives to the West are significant and merit close attention.